Characterization of two virulent phages of Lactobacillus plantarum - Briggiler Marcó, Mariángeles (2012)
We characterized two Lactobacillus plantarum virulent siphophages, ATCC 8014-B1 (B1) and ATCC 8014-B2 (B2), previously isolated from corn silage and anaerobic sewage sludge, respectively. Phage B2 infected two of the eight L. plantarum strains tested, while phage B1 infected three. Phage adsorption was highly variable depending on the strain used. Phage defense systems were found in at least two L. plantarum strains, LMG9211 and WCSF1. The linear double-stranded DNA genome of the pac-type phage B1 had 38,002 bp, a GC content of 47.6%, and 60 open reading frames (ORFs). Surprisingly, the phage B1 genome has 97% identity with that of Pediococcus damnosus phage clP1 and 77% identity with that of L. plantarum phage JL-1; these phages were isolated from sewage and cucumber fermentation, respectively. The double-stranded DNA (dsDNA) genome of the cos-type phage B2 had 80,618 bp, a GC content of 36.9%, and 127 ORFs with similarities to those of Bacillus and Lactobacillus strains as well as phages. Some phage B2 genes were similar to ORFs from L. plantarum phage LP65 of the Myoviridae family. Additionally, 6 tRNAs were found in the phage B2 genome. Protein analysis revealed 13 (phage B1) and 9 (phage B2) structural proteins. To our knowledge, this is the first report describing such high identity between phage genomes infecting different genera of lactic acid bacteria.